1990
DOI: 10.1037/0021-9010.75.5.569
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of biodata items generated from retrospective life experience essays.

Abstract: Biographical information was generated from retrospective lifehistory essays completed in the fall of 1986 by first-year students at the U.S. Naval Academy. Essays were targeted to aspects of four generic life experiences (individual accomplishments, group accomplishments, disappointing situations, and stressful situations) that might reflect the processes or outcomes of antecedent developmental episodes. Essays were coded to generate biodata items, which were then given to 917 midshipmen entering the Naval Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…In particular, professional social media sites like LinkedIn might be a useful source. Researchers (e.g., Russell et al 1990) have coded life history essays to obtain biodata, and similar procedures might be used in Internet screening. However, given the lack of standardization in Internet screening media (e.g., personal webpages), coding this information into reliably scored ratings of job applicants' work-relevant backgrounds may be impractical.…”
Section: Practical Implications Of Internet Screeningmentioning
confidence: 99%
“…In particular, professional social media sites like LinkedIn might be a useful source. Researchers (e.g., Russell et al 1990) have coded life history essays to obtain biodata, and similar procedures might be used in Internet screening. However, given the lack of standardization in Internet screening media (e.g., personal webpages), coding this information into reliably scored ratings of job applicants' work-relevant backgrounds may be impractical.…”
Section: Practical Implications Of Internet Screeningmentioning
confidence: 99%
“…To date, standardized tests have been demonstrated as valid methods for predicting college outcomes (ACT, 1997;Willingham, Lewis, Morgan, & Ramist, 1990); however, there is general agreement that these should be augmented by the assessment of other relevant attributes (U.S. Department of Education, Office of Civil Rights, 2000). The use of alternative predictors of academic achievement, including successful intelligence (Sternberg, 2004), previous experiences and biodata (Russell, Mattson, Devlin, & Atwater, 1990), and situational judgments (Lievens & Coetsier, 2002;Oswald, Schmitt, Kim, Ramsay, & Gillespie, 2004) have been proposed. However, these fail to address the plethora of research identifying numerous personality and social factors associated with college outcomes.…”
mentioning
confidence: 99%
“…This study and other recent research (e.g., Kilcullen et al 1995;Kuhnert and Russell, 1990;Mael and Hirsch, 1993;Mumford et al 1993;Russell et al 1990) underscore the growing emphasis on the role of constructs in the development of these devices (Mumford and Owens, 1987;Mumford and Stokes, 1992 Notes 1 These items are taken or adapted from Mael (1991). 2 A meta-analysis that appeared subsequently found that dominance and emotional stability were associated with leadership, but sociability was not ± need for achievement and self-confidence were not studied (Lord et al, 1986).…”
Section: Methodological Implicationsmentioning
confidence: 79%